Simultaneous degradation of hexazinone and diuron using ZrO2-nanostructured gas diffusion electrode - Carneiro, Jussara F.; Silva, Fernando L.; Martins, Alysson S.; Dias, Rafael M. P.; Titato, Guilherme M.; Santos-Neto, Alvaro J.; Bertazzoli, Rodnei [UNESP]; Lanza, Marcos R. V. [UNESP] (Elsevier B.V., 2018)
Although several authors have reported the treatment of diuron in wastewater by advanced oxidative processes (AOPs), only a handful of investigations reported using commercial herbicides composed of a mixture of active organic molecules. H2O2 is a well-known oxidant that is widely employed in AOPs and which can be produced by oxygen reduction reaction (ORR) on gas diffusion electrode (GDE). However, the development of efficient nonnoble electrocatalysts that consume less energy for ORR is still a matter of considerable interest. This study reports the electrogeneration of H2O2 on both unmodified and ZrO2-nanostructured GDE. The ZrO2-nanostructured GDE was applied toward the simultaneous degradation of hexazinone and diuron using the commercial formulation of these herbicides. The ZrO2-nanostructured and bare GDEs produced 435.6 mg L-1 and 225.8 mg L-1 of H2O2, respectively. Furthermore, an increase of 130.3% was observed in the current efficiency of oxygen reduction to H2O2 in the presence of ZrO2, indicating that less energy was consumed. Indeed, the production of 1 kg of H2O2 using ZrO2-nanostructured GDE consumes 10.2 kWh at 25 mA cm(-2), while bare GDE consumes 32.8 kWh at the same current density. Hexazinone and diuron were found to have been completely removed, albeit 28% of the organic carbon remained in solution after 120 min of electrolysis by H2O2/Fe(II)/UV. A complete removal of organic load will require longer treatment time. The residual carbon may be associated with other species present in the formulation. The results show that ZrO2-nanostructured GDE is a promising material suitable for environmental applications.
Keywords: Zirconium oxide; Nanostructured gas diffusion electrode; Hydrogen peroxide electrogeneration; Hexazinone; Diuron; Advanced oxidation process